2013
DOI: 10.1111/cen.12226
|View full text |Cite
|
Sign up to set email alerts
|

Voice problems due to virilization in adult women with congenital adrenal hyperplasia due to 21‐hydroxylase deficiency

Abstract: Subjective voice problems due to voice virilization may occur in women with CAH. This further emphasizes the importance of avoiding long periods of increased androgen levels to prevent irreversible voice changes. For these patients, we recommend referral to voice assessment and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
0
12
0
3
Order By: Relevance
“…More important though is that genetic analysis of CYP11B1 mutations confirms the diagnosis and is essential in genetic counseling similar to 21OHD [1,65]. In 21OHD, there have recently been speculations that the clinical course may be predicted and serious consequences may be prevented even in adult life by knowing the genotype [65], based on several studies from the same group [25,[68][69][70][71][72][73][74][75][76][77][78][79][80]. These aspects of different genotypes have not yet been explored in 11βOHD.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…More important though is that genetic analysis of CYP11B1 mutations confirms the diagnosis and is essential in genetic counseling similar to 21OHD [1,65]. In 21OHD, there have recently been speculations that the clinical course may be predicted and serious consequences may be prevented even in adult life by knowing the genotype [65], based on several studies from the same group [25,[68][69][70][71][72][73][74][75][76][77][78][79][80]. These aspects of different genotypes have not yet been explored in 11βOHD.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…Voice problems were related to a late CAH diagnosis and poor compliance; however, there were a few patients who had a normal voice despite compliance issues and a late diagnosis [189]. Among women with CAH, 7 % had voice problems related to virilization, but, according to the patients' own ratings of dark voice, 45 % were affected [190]. Half of the women with NCAH had a subjectively dark voice [190].…”
Section: Clinical Outcome Of Vocal Pathology In Femalesmentioning
confidence: 99%
“…Among women with CAH, 7 % had voice problems related to virilization, but, according to the patients' own ratings of dark voice, 45 % were affected [190]. Half of the women with NCAH had a subjectively dark voice [190]. Long periods of high androgen levels must be avoided, also in NCAH, to prevent irreversible voice changes and a referral for voice assessment should be considered.…”
Section: Clinical Outcome Of Vocal Pathology In Femalesmentioning
confidence: 99%
“…We have recently studied voice characteristics in women diagnosed with CAH divided according to severity in the subgroups: salt‐wasting (SW), simple virilizing (SV) and nonclassic (NC). We found that a prolonged period of under‐treatment, either due to late diagnosis or suboptimal treatment, increases the risk of severe virilization of the voice, which may concern the individual and cause distress . We have also shown that the voice virilization in women probably is due to an androgen effect on the thyroarytenoid muscle in the vocal folds, as observed with MRI examination .…”
Section: Introductionmentioning
confidence: 53%
“…Unfortunately, there are no population‐based studies that examine how vocally healthy males and females would rate satisfaction with the voice or Adam's apple. A small control group of healthy women (n = 43) gave a mean value of 81 on a 100 mm VAS (with the end‐points 0 = not satisfied and 100 = completely satisfied) when asked the question ‘Are you satisfied with your voice?’ . The BIS can be used for transmen (female sex assigned at birth, male gender identity) and transwomen (male sex assigned at birth, female gender identity).…”
Section: Discussionmentioning
confidence: 99%